2006
DOI: 10.3141/1970-08
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effect of Heat-Adhesive Emulsions for Tack Coats with Shear Test: From the Road Research Laboratory of Barcelona

Abstract: The use of conventional emulsions for tack coats can cause problems as they frequently stick to the tires of construction vehicles. Consequently the bond between the asphalt layers is inadequate. The importance of tack coats in the performance of the pavement means that bituminous emulsions are constantly being improved. Recently, new types of emulsions have been developed from very low penetration bitumen that contains no flux. They are known as "heat-adhesive" emulsions and they are resistant to construction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…The interface bonding condition between asphalt layers is one of the most important factors that affect the performance of the pavement structure and have attracted more and more attention to study the bonding testing during recent years. This leads to the development of different test devices and corresponding parameters to characterize the bonding properties in numerous papers and scientific contribution, such as layer parallel direct shear test, wedge splitting test, torque test, and pull-off test [1][2][3][4]. In China, extensive technical specifications and rules of tack coat for asphalt layers have been set up but the standard test method for evaluating the quality of layer bonding does not exist.…”
Section: Introductionmentioning
confidence: 99%
“…The interface bonding condition between asphalt layers is one of the most important factors that affect the performance of the pavement structure and have attracted more and more attention to study the bonding testing during recent years. This leads to the development of different test devices and corresponding parameters to characterize the bonding properties in numerous papers and scientific contribution, such as layer parallel direct shear test, wedge splitting test, torque test, and pull-off test [1][2][3][4]. In China, extensive technical specifications and rules of tack coat for asphalt layers have been set up but the standard test method for evaluating the quality of layer bonding does not exist.…”
Section: Introductionmentioning
confidence: 99%
“…O Ensaio de Cisalhamento LCB (Laboratorio de Caminos de Barcelona) (Figura 1-D) é um ensaio de cisalhamento com uma con iguração diferente daqueles anteriores, baseado em treŝ pontos. Miró et al (2006) explicam que para o ensaio é empregado um corpo-de-prova cilıńdrico, com diâmetro de 101,6 mm, disposto como viga sobre dois apoios afastados 200 mm entre si. Para que ocorra o cisalhamento uma força é aplicada na vertical de modo a gerar um deslocamento constante de 1,27 mm/min, cerca de 5 mm da seção de corte, para ser desprezıvel o efeito do momento letor gerado.…”
Section: τunclassified
“…Surface roughness and texture Several studies have included the surface roughness and texture as influential factors. Canestrari et al [49], Recasens et al [50,51], Tashman et al [45], Mohammad et al [39], Santagata et al [52], Leng et al [43] and Liu et al [37] realized that interface condition has direct influence on fatigue resistance. Higher strength is obtained for milled surface, with a minimal effect of the absence of tack coat applied, whereas this tack coat's absence severely decreases the strength for the non-milled sections [45].…”
Section: Surface Characteristics 321mentioning
confidence: 99%
“…Partl et al [54], Romanoschi et al [27], Mohammad et al [15], West et al [21], Recasens et al [50,51], Canestrari et al [49], Piber et al [33], Chen et al [46], Du et al [38] and Diakhate et al [29] found that temperature is an important factor. They found that temperature has a high influence on bond strength [38] and that the modulus obtained from the curve slope, the maximum shear and the coefficient of friction before the break are influenced by temperature [28].…”
Section: Temperaturementioning
confidence: 99%